2021
DOI: 10.1002/cfp2.1128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between health and household portfolio allocation

Abstract: This paper surveys the literature on the relationship between health and household portfolio allocation and provides updated empirical analysis based on recent data. Prior research finds robust evidence for cross-sectional correlations between measures of health status and portfolio decisions, but establishing the causal pathways and underlying mechanisms has proven more difficult and complex. Analysis from the most recently available 2016 and 2018 waves of the Health and Retirement Study yields results that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
1
Order By: Relevance
“…Additionally, demographic factors such as gender (Barber and Odean, 2001), race/ethnicity, and education, as well as the use of financial professions for investment advice (Lei, 2019;Shin et al, 2020) have shown a consistent impact on stock investment. Other personal characteristics, such as risk tolerance, expected health status (Keller and Siegrist, 2006;Wu, 2021;Yogo, 2016), expected investment horizon (e.g. Blanchett et al, 2018;Choi and Robertson, 2020), and personal expectation about the economy (Angelini and Cavapozzi, 2017;Grevenbrock, 2020;Zhong and Xiao, 1995) are also essential contributors in investors' Familiarity bias in direct stock investment portfolio choices.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Additionally, demographic factors such as gender (Barber and Odean, 2001), race/ethnicity, and education, as well as the use of financial professions for investment advice (Lei, 2019;Shin et al, 2020) have shown a consistent impact on stock investment. Other personal characteristics, such as risk tolerance, expected health status (Keller and Siegrist, 2006;Wu, 2021;Yogo, 2016), expected investment horizon (e.g. Blanchett et al, 2018;Choi and Robertson, 2020), and personal expectation about the economy (Angelini and Cavapozzi, 2017;Grevenbrock, 2020;Zhong and Xiao, 1995) are also essential contributors in investors' Familiarity bias in direct stock investment portfolio choices.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Desde una perspectiva de la teoría de portafolio moderna, que supone a los inversores como adversos al riesgo y por lo tanto buscan un equilibrio entre los rendimientos promedios más altos y su riesgo asociado (Markowitz, 1952). La salud es una fuente de incertidumbre y riesgo, cambios en esta pueden tener grandes impactos en el bienestar económico (Wu, 2021). Un deterioro en la salud puede afectar la asignación optima de los recursos del hogar a través de varias formas: disminución en la ingreso y riqueza asociados a una reducción en la oferta laboral y en la productividad, incremento en el gasto de servicios médicos para el diagnóstico y tratamiento de la enfermedad, así como modificar las preferencias de riesgo y crear estrategias de inversión más seguras (Decker y Schmitz, 2016; Gertler y Gruber, 2002; Wu, 2021).…”
Section: Estado Del Arteunclassified